CagA-specific Gastric CD8+ Tissue-Resident T Cells Control Helicobacter pylori During the Early Infection Phase - Koch, Maximilian R.A.; Gong, Ruolan; Friedrich, Verena; Engelsberger, Veronika; Kretschmer, Lorenz; Wanisch, Andreas; Jarosch, Sebastian; Ralser, Anna; Lugen, Bob; Quante, Michael; Vieth, Michael; Vasapolli, Riccardo; et al. (Gastroenterology, 2023)
Background & Aims: Infection with Helicobacter pylori strongly affects global health by causing chronic gastritis, ulcer disease, and gastric cancer. Although extensive research into the strong immune response against this persistently colonizing bacterium exists, the specific role of CD8+ T cells remains elusive. Methods: We comprehensively characterize gastric H pylori–specific CD8+ T-cell responses in mice and humans by flow cytometry, RNA-sequencing, immunohistochemistry, and ChipCytometry, applying functional analyses including T-cell depletion, H pylori eradication, and ex vivo restimulation. Results: We define CD8+ T-cell populations bearing a tissue-resident memory (TRM) phenotype, which infiltrate the gastric mucosa shortly after infection and mediate pathogen control by executing antigen-specific effector properties. These induced CD8+ tissue-resident memory T cells (TRM cells) show a skewed T-cell receptor beta chain usage and are mostly specific for cytotoxin-associated gene A, the distinctive oncoprotein injected by H pylori into host cells. As the infection progresses, we observe a loss of the TRM phenotype and replacement of CD8+ by CD4+ T cells, indicating a shift in the immune response during the chronic infection phase. Conclusions: Our results point toward a hitherto unknown role of CD8+ T-cell response in this bacterial infection, which may have important clinical implications for treatment and vaccination strategies against H pylori.
CRIS-Team Scopus Importer:2023-04-07
Keywords: CD8; Helicobacter pylori; Mucosal Defense; Tissue-resident T Cells